2017
DOI: 10.1016/j.jpor.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of correlation between height of residual ridge and bone density of residual ridge crest at edentulous mandible using computed tomography

Abstract: The present results suggest a negative correlation between residual bone height and the bone density of the edentulous mandibular ridge crest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…One study reported that, in alveolar crests of edentulous mandibles, bone density tends to be lower when ridges are higher (4). To inhibit progression of bone resorption in the edentulous mandible, dentures should therefore be designed to minimize bite pressure on mandibular alveolar crests.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that, in alveolar crests of edentulous mandibles, bone density tends to be lower when ridges are higher (4). To inhibit progression of bone resorption in the edentulous mandible, dentures should therefore be designed to minimize bite pressure on mandibular alveolar crests.…”
Section: Introductionmentioning
confidence: 99%
“…In edentulous patients, bone resorption progresses much faster in the mandible than in the maxilla, and the ridges of the mandible undergo a variety of changes [ 17 - 19 ]. Inouse et al [ 20 ] reported that bone density is lower in edentulous mandible alveolar crests when ridges are higher. Dentures should be designed to minimize masticatory pressure on mandibular alveolar crests to slow the progression of bone resorption in the edentulous mandible.…”
Section: Discussionmentioning
confidence: 99%
“…The impression pressure in the edentulous maxilla was studied by Frank et al, who found that it varies depending on the tray design [ 14 ]. Inoue et al investigated the effect of relief thickness on impression pressure using a clinical simulation model of an edentulous maxilla and discovered that relief equalized impression pressure in the tray [ 20 ]. When making an impression of an edentulous maxilla, Komiyama et al [ 26 ] suggested using an escape hole of 1.0 mm or larger, or a spacer the thickness of a sheet of base plate wax, to selectively reduce palatal impression pressure.…”
Section: Discussionmentioning
confidence: 99%